Wan Sip, Plante Kapten : Land Leasing on Tanna Island, Vanuatu - Nixon, Rod; Otto, Leisande; Porter, Raewyn (World Bank, Washington, DC, 2017)
The body of this report consists of five sections. Section one is an introduction to the JBE program and the context for the lease research on Tanna. Section two provides a profile of some of the relevant historical and economic features of the island and aspects related to the structure of governance and civil society organization. This is followed in section three by a summary of key findings regarding the 64 leases studied on Tanna. Section four presents more detail on the real uses of the land by analyzing the leases according to seven themes or categories: commercial or commercial tourism, schools, infrastructure, securing custom land, communications towers, agribusiness, and churches. Finally, section five discusses a small sample of non-lease-based enterprises as a preliminary study into investment decision making. Further details of the research methodology are included in the annex to the report.